2018
DOI: 10.1002/jcp.26324
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic value of circulating microRNAs in coronary artery disease: A novel approach to disease diagnosis of stable CAD and acute coronary syndrome

Abstract: Coronary artery disease (CAD) is the most common manifestation of CVD and the acute coronary syndrome (ACS) is associated with a substantial morbidity and mortality in most populations globally. There are several biomarkers for diagnosis of MI. Troponin is routinely used as a biomarker in patients with chest pain, but it lacks sensitivity in the first hours of onset of symptoms, and so there is still a clinical need for new biomarkers for the diagnosis of CAD events. Recent studies have shown that miRNAs are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…A recent study reported that serum miR‐122, miR‐140‐3p, miR‐720, miR‐2861 and miR‐3149 are increased in acute coronary syndrome (ACS) patients, and serum miR‐1, miR‐134, miR‐186, miR‐208, miR‐233 and miR‐499 are highly sensitive and specific for the diagnosis of acute myocardial infarction (AMI), and miR‐186, miR‐132 and miR‐150 are the most critical miRNAs for the diagnosis of UA 162. Moreover, plasma miR‐26a is up‐regulated in a model of AMI in mice and in human beings with ACS 117.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study reported that serum miR‐122, miR‐140‐3p, miR‐720, miR‐2861 and miR‐3149 are increased in acute coronary syndrome (ACS) patients, and serum miR‐1, miR‐134, miR‐186, miR‐208, miR‐233 and miR‐499 are highly sensitive and specific for the diagnosis of acute myocardial infarction (AMI), and miR‐186, miR‐132 and miR‐150 are the most critical miRNAs for the diagnosis of UA 162. Moreover, plasma miR‐26a is up‐regulated in a model of AMI in mice and in human beings with ACS 117.…”
Section: Clinical Value Of Mirnas As New Biomarkers For Angiogenesis‐mentioning
confidence: 99%
“…160 In addition, miR-126 and miR-92a are directly regulated by hemodynamic forces, and miR-92a can promote atherogenesis and vascular inflammation. 158 162 Moreover, plasma miR-26a is up-regulated in a model of AMI in mice and in human beings with ACS. 117 Interestingly, recent discoveries showed that circulating miR-214 was up-regulated in the early phase after AMI but then gradually decreased to near normal levels.…”
Section: Other Mirnas In Angiogenesismentioning
confidence: 99%
“…microRNAs (miRNAs or miRs) are small, single‐stranded, nonprotein‐coding ribonucleic acids (RNAs) composed of approximately 19–22 nucleotides long . miRNAs can be found in different body fluids . These short‐fragment RNAs acting as posttranscriptional regulators of gene expression play pivotal roles in many biological processes and cellular pathways including cell cycle progression, proliferation, differentiation, apoptosis, and angiogenesis .…”
Section: Role Of Micrornas In Targeting C‐met/hgf Signaling Pathwaymentioning
confidence: 99%
“…There is evidence of an association between the expression of microRNA (miRNA or miR) and regulation of TLRs-mediated signaling (18). miRNAs are short, non-coding RNA comprised of 19-22 nucleotides which play key roles in posttranscriptionally regulation of many biological activities in the cells such as gene expression in cardiovascular and immune system cells (1). In this regard, Taganov et al observed that TLR4 ligand could be able to increase miR-132, miR-146a and miR-155.…”
Section: Toll-like Receptors Signaling and Its Association With Micrornamentioning
confidence: 99%
“…Cardiovascular disease (CVD) is a major health problem with a high prevalence of morbidity and mortality worldwide, and particularly in developing countries. Over the last decade, the prevalence of CVD has risen alarmingly and it is now estimated that about 17 million deaths, and a very high rate of complications result from CVD and this imposes huge economic burden on healthcare system (1,2). Ischemic heart disease and cerebrovascular disease are responsible for a large percentage of patients with CVD (3).…”
Section: Introductionmentioning
confidence: 99%